Liver Functions in the Treatment of Severe Exotoxic Shock: Experimental Study - N. V. Shapovalova; Yu. V. Struk; T. N. Sviridova; Ye. A. Tarannikova; Ye. M. Shamayev (Общая реаниматология)
The paper presents experimental findings and assesses the results of liver function tests and survival rates in 60 dogs with severe exotoxic shock (SES) in the use of different intensive therapy modes. The results of the study lead to the conclusion that multicomponent intensive therapy, including auxiliary circulation in combination with extracorporeal oxygenation and blood exchange (exfusion-and-transfusion therapy), is the method of choice in treating SES. The multicomponent therapy is recommended for use in the clinical practice of resuscitation and toxicology centers.